Dose response effects of carbohydrate nature of lyophilized leaf powder of Azadirachta indica on testis of albino rats - Pattan, Kalpana I; Ghodesawar, MukhtarAhmed G; Aladakatti, Ravindranath H (International Multidisciplinary Research Journal, 2013)
The purpose investigation is designed to investigate the effect of carbohydrate nature of lyophilized Azadirachta indica leaf powder on the histology of testis, since experimental studies shown that the chemical nature of leaf powder was studied and observed that the leaf powder was carbohydrate-rich in nature. In the present study of histomorphometric and histopathological dose dependent assessments of carbohydrate nature of lyophilized A.indica leaf powder on the testis of male wistar rats given 25, 50 and 75 mg in suspension of 1 mL Propylene Glycol, respectively/kg body weight, once daily, orally, for 24 days showed varying degrees of desquamation of seminiferous epithelial cells, degeneration of seminiferous tubules and presence of large-sized multinucleated cells as well as the spermatogenesis was arrested either at the primary spermatocytes or the spermatogonial stages. Damaged seminiferous tubules contained the abundance of vacuoles with varying size Total count, cell and nuclear diameter of spermatogonia, spermatocytes, spermatids and Leydig cells were reduced in a dose dependent manner (P ≤ 0.05). From the results obtained, it can be observed such effects on the testis are possibly due to curtailing of androgen supply within the testis or it may be a direct effect of this carbohydrate-rich nature of lyophilized A. indica leaf powder on the tissue probably due to direct or indirect gonadotrophic hormone deficiency.